Analisis Nilai-Nilai Karakter pada Cerita Rakyat Nias dalam Buku Sadieli Telaumbanua Edisi 2018 - Nosnidar Gulo; Noibe Halawa; Yanida Bu’ulolo; Lestari Waruwu (Jurnal Simki Postgraduate, 2026)
This study aims to identify and describe the character values contained in Nias folktales found in the book by Sadieli Telaumbanua, 2018 edition. The study employed a qualitative approach using a descriptive method. The data source consisted of Nias folktale texts contained in the book. Data were collected through documentation study and analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that the Nias folktales contain various character values, including religiosity, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, patriotism, appreciation of achievement, friendliness or communicative attitude, peace-loving attitude, reading interest, environmental care, social care, and responsibility. Among these values, hard work and responsibility were the most dominant. The findings indicate that Nias folktales serve not only as a form of entertainment but also as a medium for character education containing moral and cultural values that are important to be passed on to younger generations. Therefore, Nias folktales can be utilized as a source of local wisdom-based character education in educational settings.